PENGAMATAN PELAKSANAAN PEKERJAAN STRUKTUR KOLOM PADA PROYEK GEDUNG TERPADU PSIKOLOGI OLAHRAGA UNIVERSITAS NEGERI SURABAYA DI PT. NINDYA KARYA - Aprillia Rachmayanti (Jurnal Vokasi Teknik Sipil, 2024)
This article presents the findings of an internship report carried out on the Unesa Sports Psychology Integrated Building construction project with the aim of analyzing and evaluating the project. The contents of the report include an in-depth analysis of the column structure. Columns act as the main vertical elements that distribute the building load to the ground base, a deep understanding of the behavior and structural characteristics of columns is essential in ensuring the success of the project. The approach applied includes data and information collection, structural modeling using special software and analysis of the load and strength of column structures. The results of the analysis show that the column structure in the Unesa Sports Psychology Integrated Building construction project meets the specified strength and stability requirements. It is hoped that this Work Practice Internship report and article can make a positive contribution to developing knowledge about column structures and improving safe and efficient construction practices in the future.